(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The French language is rich in expressions of politeness and courtesy. These formulas play a crucial role in social interactions, reflecting respect and consideration towards others. Their appropriate use can change the atmosphere of a conversation and contribute to harmonious relationships. In this article, we will offer a selection of useful phrases to start a conversation in French, exploring various ways to express requests or wishes elegantly using appropriate grammatical structures such as le Conditionnel and polite expressions.